From rehabilitation to penal communication: The role of furlough and visitation within a retributivist framework. (July 2021) - Bülow, William; Dagan, Netanel
Retributivism is one of the most prevalent theories in contemporary penal theory. However, despite its popularity it is frequently argued that too little attention has been paid to the implications of retributivism for prison management and prison life, including prison visits and furlough. More so, it has been questioned both whether the various forms of retributivism found in the philosophical literature on criminal punishment have anything to say about what prison life ought to be like and whether they are able to criticize deeply contested rules and practices, such as those that deny inmates contact with family-members for the sake of prison discipline. In this paper, we argue that prison visits and furlough have a crucial role in a prison system based on retributivist principles. In particular, we argue that the communicative theory of punishment has important theoretical resources for proving a strong and compelling rationale for both furlough and visitation on retributivist grounds. Besides exploring this rationale, we also discuss the practical implications of this view for the penal policy.